2021
DOI: 10.1002/mds.28602
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Confocal Microscopy Identifies Parkinson's Disease with More Rapid Motor Progression

Abstract: A BS TRACT: Background: Corneal confocal microscopy (CCM) is a noninvasive, reproducible ophthalmic technique to quantify corneal small nerve fiber degeneration. CCM demonstrates small nerve fiber damage in Parkinson's disease (PD), but its role as a longitudinal biomarker of PD progression has not been explored. Objective: The aim of this study was to assess corneal nerve morphology using CCM in relation to disease progression in PD. Methods: Sixty-four participants with PD were assessed at baseline and at 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 47 publications
5
22
0
Order By: Relevance
“…In a recent study from China, CNFD showed an excellent diagnostic performance with a AUC of 0.96 for PD and corneal nerve fiber parameters correlated with the severity of motor symptoms measured using the H-Y stage, UPDRS-III and UPDRS-Total ( 81 ). Furthermore, we have shown that a lower corneal nerve fiber length predicts progressive worsening of UPDRS-III over 12 months in patients with PD ( 82 ). CCM could therefore add to the diagnostic toolbox for pre-motor Parkinson's disease.…”
Section: Ccm In Central Neurodegenerative Diseasesmentioning
confidence: 92%
“…In a recent study from China, CNFD showed an excellent diagnostic performance with a AUC of 0.96 for PD and corneal nerve fiber parameters correlated with the severity of motor symptoms measured using the H-Y stage, UPDRS-III and UPDRS-Total ( 81 ). Furthermore, we have shown that a lower corneal nerve fiber length predicts progressive worsening of UPDRS-III over 12 months in patients with PD ( 82 ). CCM could therefore add to the diagnostic toolbox for pre-motor Parkinson's disease.…”
Section: Ccm In Central Neurodegenerative Diseasesmentioning
confidence: 92%
“…We have confirmed corneal nerve fibre loss in PD [ 74 ], with CNFD demonstrating excellent diagnostic utility [ 75 ]. A lower CNFL predicts progressive worsening of UPDRS-III over 12 months in patients with PD [ 76 ], suggesting the application of CCM in diagnosing pre-motor PD.…”
Section: Ccm In Central Neurodegenerative Diseasementioning
confidence: 99%
“…The validation strategies used for clinical scales and questionnaires, where a new instrument must correlate with another already-validated measure, may not be sufficient for the validation of AI-generated outputs. While recognizing that the use of a “biomarker” identified from a population might not be appropriate for application to an individual [ 8 ], researchers may still need to compare AI outputs with those of established techniques such as quantitative MRI/SPECT [ 9 ], corneal confocal microscopy [ 10 ], camera tremor magnification [ 11 ], and retinal nerve fiber layer thickness [ 12 ].…”
Section: Validationmentioning
confidence: 99%